(untitled) (Research, Society and Development, 2023)
An aneurysm is defined as the abnormal and localized dilation of a blood vessel, which can be congenital or acquired. The main consequence is vessel rupture, leading to hemorrhage, hypovolemic shock, and subsequent sudden death. Clinical signs can also be silent or resemble other pathologies, making the diagnosis complex. This study aims to report the clinical case of a Criollo mare diagnosed with an aneurysm of the left external iliac artery, as well as the treatment and diagnostic methods. During the anamnesis, it was observed that the patient experienced episodes of acute abdominal discomfort with rapid and spontaneous resolution, anorexia, and progressive weight loss for approximately a year. Musculoskeletal evaluation revealed grade III lameness in the left pelvic limb. Rectal palpation revealed a parasagittal increase in volume near the lumbosacral segment with a palpable pulse in the region of the left abdominal aorta. Rectal ultrasound with a linear probe (5.5 MHz) revealed decreased and retrograde blood flow compared to the contralateral vessel, suggesting an aneurysm of the left external iliac artery. The prescribed treatment involved the administration of acepromazine, omeprazole, and acetylsalicylic acid for 90 days. Ultrasonography was essential for the final diagnosis and resolution of the reported case, along with the combination of drugs described in the therapeutic protocol.